Charge Transporting Materials Grown by Atomic Layer Deposition in Perovskite Solar Cells - Young Joon Cho; Min Ji Jeong; Ji Hye Park; Weiguang Hu; Jongchul Lim; Hyo Sik Chang (Energies, 2021)
Charge transporting materials (CTMs) in perovskite solar cells (PSCs) have played an important role in improving the stability by replacing the liquid electrolyte with solid state electron or hole conductors and enhancing the photovoltaic efficiency by the efficient electron collection. Many organic and inorganic materials for charge transporting in PSCs have been studied and applied to increase the charge extraction, transport and collection, such as Spiro-OMeTAD for hole transporting material (HTM), TiO2 for electron transporting material (ETM) and MoOX for HTM etc. However, recently inorganic CTMs are used to replace the disadvantages of organic materials in PSCs such as, the long-term operational instability, low charge mobility. Especially, atomic layer deposition (ALD) has many advantages in obtaining the conformal, dense and virtually pinhole-free layers. Here, we review ALD inorganic CTMs and their function in PSCs in view of the stability and contribution to enhancing the efficiency of photovoltaics.